Discourse of the British press as the main factor of the formation of conceptual vision of the world - Y. V. Akimtseva (Дискурс профессиональной коммуникации, 2019)
Discourse is one of the basic notions in linguistics due to its specificity which lies in representation, interpretation and conceptualization of any activity including professional one. In the host of institutional discourse types media discourse is quite prominent as it provides a communicative and cognitive representation of professional or other activities and reflects a combination of conceptual, linguistic, extralinguistic, sociocultural, pragmatic, psychological and cognitive features of the media product author and the consumer (both individual and society as a whole). The research shows that the main functional component of the media discourse is actualized in the informative and impact function, with impact tending to prevail. From this perspective the involvement of the British press discourse in building up the recipient’s conceptual vision of the world is analyzed; the article exemplifies linguistic means of explicit or implicit instilling in readers’ minds of the addresser’s subjective interpretation of information instead of presentation of pure facts. This leads to the inference about an inextricable connection between the conceptual and the discursive world pictures.The article contains the press discourse typology based on cognitive and sociocultural criteria. The most interesting representatives of the binary opposition of the press discourse types are the discourse of the British quality press and the discourse of the British popular press. The author discloses three aspects (stylistic, structure- and content-related, pragmatic) of the British press specificity exemplifying them by the analysis of sample texts of both types. The revealed features of the said discourse types are compared, and certain findings are presented on the identity and difference in their use of tools of the author’s intention verbalization. The main tools of verbalization are linguistic means of expression, recurrent constructions, modal constructions, introductory words, contracted negative forms and others.